Burkholderia cenocepacia bacteremia in the oncology clinic: clinical features and outcomes - I. A. Kurmukov; A. M. Pronina; Sh. R. Kashiya; N. S. Bagirova; N. V. Dmitrieva; Z. V. Grigor’yevskaya; I. N. Petuhova; I. V. Tereshchenko (Журнал инфектологии)
Aim of the study: To determine clinical course of Burkholderia cenocepacia bacteremia and outcomes in patients receiving cancer therapy. Materials and methods: We indentified 10 adult patients with culture-verified catheter-related Burkholderia cenocepacia bacteremia. Pathogens were identified with protein mass spectrometry of bacteria cells. Testing for the «Microscan WalkAway 40/96 Plus» (Germany) did antibiotic sensitivity or «VITEK 2» (France). Results: In the majority of cases course of bacteremia was indolent; this fact precluded its rapid identification with standard procedures for diagnosing bloodstream infection. All patients developed fever but we revealed neither leukocytosis nor leucopenia which could be attributed to active infection. However, antibiotic treatment was initiated during the 24 h after the first signs of infection in all cases. In one patient bacteremia was complicated with septic shock. We revealed that Burkholderia cenocepacia was able to form biofilms and persist in implanted venous port systems after treatment and in order to eradicate the pathogen venous catheters had to be removed despite effective antibacterial treatment. Initial treatment was prescribed empirically and further antibacterial treatment was adjusted based on sensitivity testing results in 7 patients. Burkholderia cenocepacia eradication rate was 100% and all patients were cured and were able to continue prescribed cancer therapy afterwards. Conclusion: given to the low frequency of Burkholderia cenocepacia sporadic infections, clinicians must be aware of the possibility of drugs and medical supplies contamination with this pathogen. If one reveals ≥1 case of Burkholderia cenocepacia-associated infection the internal investigation must be initiated. Empiric antimicrobial therapy widely prescribed to treat febrile neutropenia in cancer patients is effective in these cases. However, it cannot eradicate the pathogen from inner lumen of implanted venous catheters. Identification of the possible pathogen in blood cultures and antibiotics sensitivity testing using microbiological analyzers prompts the diagnosis of bacteremia and prescription of most effective therapy